Feminisation of Poverty in India - Visalakshmi, S.; G.N, Sumathi; Kar, Rohitanshu (International Journal of Engineering and Technology, 2018)
The purpose of the paper is to explore link between the phenomenon of feminization of poverty and the social factors affecting it. The analysis used the existing data and the assertions have been made based on conceptual grounds. This paper highlights the gender dimension of poverty, which results in increasing proportions of the female poor in the country. Gender-based hardships and segregations are adding up to poverty-related vulnerabilities. The collaborative result of gender and indigence were ascertained by analysing women’s demographics, educational and employment conditions.